Erectile dysfunction among patients with chronic brucellosis. Issue 5 (October 2018) - Safwat, Ahmed; Hasanain, Ahmad; Mahran, Ali; Bakkar, Sally; Abdel-Aal, Sherif; Nafee, Amany
Abstract Objective Only a single study investigated erectile dysfunction (ED) among patients with chronic brucellosis without including a control group. Our study objective was to determine the prevalence of ED among patients with chronic brucellosis compared to normal subjects, and to explore the predictors of ED. Materials and methods We included 93 chronic brucellosis patients and 92 subjects as a control, from June 2013 to August 2017. Chronic brucellosis was diagnosed based on persistent symptoms for ≥1 year with positive immunoglobulin G antibody titer (≥1:160) by standard tube agglutination test; the mean duration was 21 ± 6.2 months. Clinical evaluation (including an Arabic validated version of the five-item International Index of Erectile Function to diagnose ED; score of 5–21 was diagnostic), imaging studies (including scrotal ultrasonography) and laboratory investigations (including estimation of fasting serum level of glucose (after fasting for 8 h), lipids profile (after fasting for 14 h), and serum level of testosterone) were conducted. A fasting serum glucose level of ≥ 7 mmol/L defined diabetes mellitus (DM). Predictors of ED were identified using multivariate analysis (binary logistic regression). Results The mean age of patients was 35.4 ± 13.7 years; 24.7% of them had DM, while low serum level of testosterone was detected among 54.8%. Among the patients, ED was significantly more frequent compared to the control subjects (69.9% vs. 19.6%, p  < 0.001). Low serum level of testosterone (OR 4.8, 95% CI 1.7–29.3, p 0.008), and DM (OR 3.5, 95% CI 1.2–34.6, p 0.011) were the predictors of ED among the patients. Conclusions The prevalence of ED among patients with chronic brucellosis is high. Low serum level of testosterone and DM are associated with ED among such patients.